Kobiety na Politechnice Lwowskiej - Strojna-Krzystanek, Anna (Studia Edukacyjne, 2019)
The author of the article wants to picture the education opportunities for females in the 19th and 20th centuries at higher education institutions. The article brings forward the characters of women associated before World War II with the oldest technical university in Poland, the Lviv Polytechnic, detailing their contribution to the development of Polish science.